2014
DOI: 10.1128/jcm.00189-14
|View full text |Cite
|
Sign up to set email alerts
|

Human Cathelicidin LL-37 Resistance and Increased Daptomycin MIC in Methicillin-Resistant Staphylococcus aureus Strain USA600 (ST45) Are Associated with Increased Mortality in a Hospital Setting

Abstract: Bacteremia caused by methicillin-resistant Staphylococcus aureus (MRSA) USA600 has been associated with increased patient mortality. We found that USA600 MRSA exhibited significantly increased resistance to human cathelicidin LL-37 killing and daptomycin MIC creep compared to non-USA600 MRSA. Virulent health care-associated MRSA strains may coevolve innate host defense peptide and antibiotic resistances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In order to minimize the potential for confounding phylogenetic differences, we focused on ST45/USA600 MRSA, a lineage found in Detroit, Michigan that is associated with increased all-cause mortality [16]. Forty-four well-characterized sequential ST45/USA600 isolates with documented clinical outcomes [17] were identified and selected for this study. Of these 44 isolates, 21 were isolated from patients who survived the infection, and 23 were isolated from decedents.…”
Section: Methodsmentioning
confidence: 99%
“…In order to minimize the potential for confounding phylogenetic differences, we focused on ST45/USA600 MRSA, a lineage found in Detroit, Michigan that is associated with increased all-cause mortality [16]. Forty-four well-characterized sequential ST45/USA600 isolates with documented clinical outcomes [17] were identified and selected for this study. Of these 44 isolates, 21 were isolated from patients who survived the infection, and 23 were isolated from decedents.…”
Section: Methodsmentioning
confidence: 99%
“…In stark contrast to vancomycin, which enjoyed decades of resistance-free use, alternative therapies like daptomycin, linezolid, telavancin, third generation cephalosporins (for example, ceftaroline) and the glycylcycline tigecycline antibiotic classes have led to resistance soon after their clinical introduction. 110 Resistance via impediment of glycopeptide access A significant body of work has been devoted to the identification of mutations delineating the genetic differences between VSSA and VISA. 79,83,111,112 Although considerable genetic and transcriptional variability between different lineages results in a myriad of phenotypic outcomes, cell wall aberrations are a feature observed consistently in response to the physiological stress imposed by antibiotic treatment.…”
Section: Vancomycin Resistance and Heteroresistancementioning
confidence: 99%
“…Comparison of MSSA with MRSA strains revealed that MRSA strains were less susceptible to AMPs (15). Indeed, numerous studies have shown a correlation between methicillin and human cathelicidin LL-37 resistance (76,88,108). Moreover, staphylococcal metalloproteinase aureolysin can cleave LL-37, and iron-regulated surface protein A (isdA) can impart resistance to human β-defensin 2 (13,95).…”
Section: Staphylococcus Pseudintermediusmentioning
confidence: 99%